Association Between Typhoid and Paratyphoid Fever with ABO Blood Group among Patients Attending Raparin Pediatric Hospital in Erbil - Hadi Alchawishli, Khanzad; Abdulla Palpitany, Sadiya; Sadiq Smail, Banaz; Salem Hassan, Shukir (Diyala Journal of Medicine, 2019)
Background: The ABO blood groups and Rhesus factor are different in their susceptibility and resistance to various diseases. The role of ABO blood group has long been a subject of investigation and debate. Typhoid and paratyphoid disease is commonly encountered a systemic disease caused by gram negative bacteria Salmonella typhi and Salmonella paratyphi. Because of the presence of favorable predisposing factors for transmission of typhoid disease among children in Kurdistan. Objective: To find the occurrence of Salmonella typhi and Salmonella paratyphi among children, with their distribution among different blood groups. Patients and Methods: A cross-sectional study was carried out on 300 subjects were randomly selected from children who were likely to be infected with typhoid or paratyphoid fever in Raparin Teaching Hospital in Erbil. Blood sample were taken for performing ABO blood grouping, widal test and blood cultures. Results: Result of the study reveals (31.33%) and (34.33%) of children were infected with Salmonella typhi and Salmonella paratyphi. The highest typhoid/paratyphoid was observed among blood group O, thus it was most susceptible group. The least was noticed among blood group AB children which is the most resistant. Conclusion: Results have revealed significant association between ABO blood group and susceptibility to typhoid/paratyphoid infections. DOI:https://doi.org/10.26505/DJM.17024590317